Analisis Kinerja Keuangan Pada Pemerintah Daerah Kabupaten Banggai Kepulauan Tahun 2018-2022: Financial Analysis of the Regional Government of Banggai Islands Regency 2018-2022 - Ariwijaya, Heny; Nursin, Depianti; Husen, Sri Rahayu; Muangi, Mario K (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
This study aims to determine the financial performance of the Banggai Islands Regency Government for the 2018-2022 period using fiscal decentralization ratio analysis, independence ratio, effectiveness ratio, harmony ratio, efficiency ratio, growth ratio. The type of data used in the study is quantitative descriptive data which is intended to use quantitative data obtained using documentation techniques. The data analysis method uses financial ratio analysis. The results of this study indicate that the Banggai Islands Regency Government has not been optimal in managing regional finances. Although the realization of its budget has been effective and quite efficient, the growth of Regional Original Income is due to the priority of regional spending. Most prioritize operating expenses over capital expenditures.